TESOL Quarterly Research Guidelines. Issue 1 (25th January 2016) - Mahboob, Ahmar; Paltridge, Brian; Phakiti, Aek; Wagner, Elvis; Starfield, Sue; Burns, Anne; Jones, Rodney H.; De Costa, Peter I.
Abstract : This article provides research guidelines for authors intending to submit their manuscripts to TESOL Quarterly . These guidelines include information about the TESOL Quarterly review process, advice on converting a dissertation into a research article, broad introductions to a number of research methods, and a section on research ethics. The research methods discussed here are experimental research, survey research, ethnographic research, discourse analysis, and practitioner research. These are, of course, not the only methods that authors draw on for their submissions to TESOL Quarterly but ones we thought it would be helpful to provide advice on. Each of the sections on research methods includes a broad introduction to the method (or approach), a guide for preparing a manuscript using the particular method or approach, and an analysis of an article published in TESOL Quarterly using that method or approach.